2011
DOI: 10.1097/med.0b013e32834a8764
|View full text |Cite
|
Sign up to set email alerts
|

The possible roles of environmental factors and the aryl hydrocarbon receptor in the prevalence of thyroid diseases in Vietnam era veterans

Abstract: The balance between T(reg), T(h)17 and T(h)22 cells is disrupted by TCDD, resembling what has been found clinically in Graves' disease and Hashimoto's thyroiditis, and in animal models of these diseases. By altering the immune balance in susceptible individuals, chronic TCDD exposure may influence the prevalence of autoimmune thyroid diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…For example, Vietnam War Veterans exposed to the Agent Orange descendants may currently be experiencing an increased incidence of disease [7]. The toxic effects of direct exposure to dioxin include acute liver damage, weight loss, thymic atrophy, immune suppression and chronic diseases, as well as lymphomas and leukemias in humans [6]. The list of diseases seen following exposure of war veterans to Agent Orange (herbicide contaminated with dioxin) during the Vietnam era is growing [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Vietnam War Veterans exposed to the Agent Orange descendants may currently be experiencing an increased incidence of disease [7]. The toxic effects of direct exposure to dioxin include acute liver damage, weight loss, thymic atrophy, immune suppression and chronic diseases, as well as lymphomas and leukemias in humans [6]. The list of diseases seen following exposure of war veterans to Agent Orange (herbicide contaminated with dioxin) during the Vietnam era is growing [7].…”
Section: Discussionmentioning
confidence: 99%
“…In rodents TCDD has a half-life of weeks and causes liver disease, weight loss, thymic atrophy and immune suppression. In humans direct dioxin exposure influences chronic diseases, lymphomas and leukemias [6]. The half-life of TCDD in humans varies to over 10 years with body mass index, age, sex and exposure concentration [7].…”
Section: Introductionmentioning
confidence: 99%
“…), thyroid hormones or adrenal cortical functions (Han et al . ; Spaulding ; Leijs et al . ) among others, that could contribute to the observed impairments in SGZ NPC maturation and hippocampal function (Desouza et al .…”
Section: Discussionmentioning
confidence: 99%
“…In another longitudinal study, it was shown that serum TCDD levels were correlated with serum TSH levels . It was further shown that Vietnam veterans have an up to 3.5‐times increased risk of hyperthyroidism, hypothyroidism and Grave's disease several years after initial exposure …”
Section: Discussionmentioning
confidence: 97%
“…42 It was further shown that Vietnam veterans have an up to 3.5times increased risk of hyperthyroidism, hypothyroidism and Grave's disease several years after initial exposure. 43 The tumorigenic potential of dioxins has been described in the literature, and TCDD is now classified as a human carcinogen by the International Agency for Research on Cancer (IARC) based on animal and human observational studies; in particular, non-Hodgkin lymphoma is particularly frequent. 44,45 However, this remains controversial as the evidences for a relationship between TCDD and human carcinogenesis are indirect.…”
Section: Discussionmentioning
confidence: 99%